PERAN PEMBERIAN HARGA DALAM MENINGKATKAN VOLUME PENJUALAN PADA TOKO JENITRA SNACK DI BINTARO SEKTOR 7 TANGERANG SELATAN - Lani Kusuma; Purwanti (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the role of pricing in increasing sales volume at The Jenitra Snack Store in Bintaro Sektor 7, South Tangerang. The type of research used is Qualitative. By emphasizing the interview method to key informants, where the key informants here are shop employees and consumers, the triangulation technique is source triangulation, technical triangulation and time triangulation, supported by secondary and primary data collection procedures. The validity of the study was tested with several tests, namely Credibility, Compliability, Distributability, and Transferability. The results of this study indicate that the Role of Pricing is very important in increasing Sales Volume at the Jenitra Snack Store in Bintaro Sektor 7, South Tangerang. So the market must always consider the quality and the right price for a product sold at the Jenitra Snack store.